Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/ons/opy002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intranasal Flap Perfusion by Intraoperative Indocyanine Green Fluorescence Angiography

Abstract: ICG fluorescence angiography of intraoperative flap perfusion is feasible and correlates well with outcomes of postoperative MRI flap enhancement and flap necrosis. Additional study is needed to further refine the imaging technique and optimally characterize the clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…34 Geltzeiler et al 19 concluded that lack of flap enhancement (with both intraoperative ICG angiography and imaging) is associated with postoperative necrosis of pedicled intranasal flaps. The observations of this study reinforce the findings of Geltzeiler et al 19 ICG has been demonstrated by certain groups to be a costeffective strategy that can assist in head and neck reconstruction excellent survival outcomes. 19,35 Cost per injection of ICG is U.S. $222 per 25-mg vial of ICG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Geltzeiler et al 19 concluded that lack of flap enhancement (with both intraoperative ICG angiography and imaging) is associated with postoperative necrosis of pedicled intranasal flaps. The observations of this study reinforce the findings of Geltzeiler et al 19 ICG has been demonstrated by certain groups to be a costeffective strategy that can assist in head and neck reconstruction excellent survival outcomes. 19,35 Cost per injection of ICG is U.S. $222 per 25-mg vial of ICG.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,22,24,25,29,30 Multiple attempts were made to retrieve full-text articles; however, no response was received from the authors. The literature search protocol for selection of eligible studies is presented as a PRISMA flow diagram in ►Fig.…”
mentioning
confidence: 99%
“…28 Fixed doses in head and neck reconstruction have also been reported according to the region assessed, which include 5 mg in forehead flaps and supraclavicular flaps, 1,22,25 6.25 mg in deep plane facelift, 29 7.5 mg in radial forearm and fibula free flaps, 30 10 mg in salvage laryngectomy, 14 12.5 mg in anterolateral thigh flaps, 31 and up to 25 mg in nasoseptal flaps. 32,33 After the bolus is injected in a central or peripheral line, usually a 10-mL 0.9% normal saline flush is administered.…”
Section: Icg Dosing In Head and Neck Reconstructionmentioning
confidence: 99%
“…3 Endoscopic use has also been of value in skull base reconstruction, showing that fluorescence of the pedicle and the flap together was associated with 100% success of flap survival when evaluated postoperatively with MRI (magnetic resonance imaging) contrast enhancement, although absent pedicle fluorescence may require modifications or an alternate flap. 32,33…”
Section: Fistula Prediction After Salvage Surgerymentioning
confidence: 99%
“…18 In addition, E-ICG has been suggested as a tool to enhance visualization of vasculature, assessment of blood supply to nasoseptal flaps, and tumor identification. 17,[19][20][21][22] Some investigators have concluded that there is a correlation between tumor fluorescence and radiological enhancement on T1-weighted gadolinium-enhanced (T1WGd) MR images. 2,9 To our knowledge, however, there have been no described criteria for the selection of cases in which E-ICG may be useful, and there has been no quantitative correlation of fluorescence to preoperative imaging.…”
mentioning
confidence: 99%